Effects of Previous Fall–Winter Crop on Spring–Summer Soybean Nutrition and Seed Yield under No-Till System - Soratto, Rogério P. [UNESP]; Guidorizzi, Fernando V. C. [UNESP]; Sousa, Westefann S. [UNESP]; Gilabel, Amanda P. [UNESP]; Job, André L. G. [UNESP]; Calonego, Juliano C. [UNESP] (MDPI, 2022)
Interest in fall–winter species options for rotation with soybean (Glycine max (L.) Merr.) has arisen; however, little is known about how they can affect the performance of subsequent soybean under a no-tillage system in tropical environments. Our objective was to evaluate the leaf nutrient concentration, aboveground dry matter (DM) accumulation, macronutrient uptake, yield components, and seed yield of soybean cropped in succession to different crop species. Consequently, a field experiment was conducted during three consecutive growing seasons in Botucatu, São Paulo State, southeastern Brazil. The experiment was arranged in a randomized complete block design with four replicates. The treatments consisted of the cultivation of five crops (crambe (Crambe abyssinica Hochst. ex. R.E. Fries), maize (Zea mays L.), safflower (Carthamus tinctorius L.), sorghum (Sorghum bicolor (L.) Moench), and sunflower (Helianthus annuus L.)) in rotation with soybean, in addition to plots that lie fallow (spontaneous weeds) in the soybean off-season, totaling six treatments. Letting plots lie fallow during the off-season reduced the DM accumulation, nutrient uptake, and seed yield of the soybean crop in succession. Preceding cultivation of fall–winter crambe or sunflower favored the uptake of P, K, Ca, Mg, and S by the following soybean crop. The cultivation of sorghum, safflower, and crambe as fall–winter crops also increased the seed yield of subsequent soybean (from 12 to 18% on the average of three growing seasons) compared to fallow plots. The highest increases in soybean seed yield were found in succession to maize (37%) or sunflower (45%) in the second and third growing seasons, respectively.
Keywords: crop rotation; double-crop system; Glycine max; nutrient uptake; seed yield